Precise farming and monitoring of agriculture through drone - BHARTI, SANDEEP; ., MEETALI; BHARTI, DEEPSHIKHA (Journal of Soil and Water Conservation, 2021)
With the advent of drones, monitoring of farming has become easier and cost effective. The Unmanned aerial vehicles (UAVs), or drones have become a popular technology for the application of amounts of inputs like water, fertilizers, pesticides etc. at the correct time to the crop for increasing its productivity and maximizing its yields. Global Positioning System (GPS) technology is extensively used in precision agriculture. Drones are now a leading technology in agriculture which is set to invade agricultural world. The miniature unmanned aircrafts can be piloted by remote control from the ground by the operator via a computer program and can reach speeds of up to 50 km/h. These machines have a battery life of anywhere between 15 to 25 minutes of flight time and can reach ranges of as far as a kilometer away from the operator. Drone helps to keep a track on crop position, control farm subsidies, detect pests, monitor nutritional and water stress on the crops, and they can even spray fertilizer and pesticides on the crops from above. The use of this 21st century technology for the sake of agriculture is commendable and it will directly help farmers in the long run. We might find a lot of drones flying over the agricultural fields in the coming future and it will also double as a scarecrow.